(untitled) (International Journal of Engineering and Computer Science, 2013)
This paper presents the application of dynamic voltage restorers (DVR) on power distribution systems for mitigation of voltage sags, harmonics and imbalances at sensitive loads. The dynamic voltage restorer (DVR) has become popular as a cost effective solution for the protection of sensitive loads from voltage sags and swells. It would be advantageous that a DVR could also be used to compensate any steady state load voltage harmonics, since this would increase the Power Quality. The DVR, which is based on a five-level flying-capacitor voltage Source converter (VSC), has been proved suitable for the task of compensating voltage disturbances. The performance of the DVR depends on control technique involved. This paper presents the control system based on the so-called repetitive control. Unlike other control schemes with a comparable range of applicability, only one controller is needed to cancel out all three disturbances simultaneously, while exhibiting good dynamic performance. Simulation results are presented to illustrate and understand the performances of DVR in supporting load voltage. To evaluate the quality of the load voltage during the operation of DVR, Total Harmonic Distortion (THD) is calculated.